Seasonal variability in cod target strength - Ona, Egil (ICES, 2006)
The acoustic target strength of adult cod (Gadus morhua) was measured ex situ in a large, 4500 m3, experimental net pen at the IMR Austevoll aquaculture station in eight periods between November 1996 and May 1998. A calibrated Simrad EK500 split beam echo sounder was used to collect the acoustic data from a vertically observing transducer, positioned in the middle of the 21 m deep net pen. Groups of about 20 individual cod were transferred from the control storage population in each measurement series, but moved in every other aspect freely within the experimental net pen during the acoustic measurements. Natural variations in gonadosomatic index as well as changes in condition factor from an enforced starvation was monitored and correlated with changes in target strength. A General Linear Model (GLM) was used to estimate the functional relationship between the target strength at 38 kHz and important biological parameters. The significant ones were: Condition factor (CI), Liver index (LI), the spread of the tilt angle distribution (SDTILT), while the gonadosomatic index (GSI) mean swimming angle (MT) and the swimbladder index (SI) was not significant. For cod between 50 and 60 cm size, the target strength relationship is suggested to be: = 20 log L – 64.0 – 0.099(SDTILT) + 2.44(LI) – 1.86(CI) , where the effect of tilt angle may be converted to a day/night effect. Under normal liver index and condition factor, the new mean target strength is slightly higher than the one used in the surveys, but correspond well to the experimental nighttime observations. The ex situ data are compared with recent in situ target strength measurements.